A neutralidade concorrencial no Direito Constitucional Tributário brasileiro - Federighi, André Catta Preta (2022)
An integrated analysis of the constitutional norms related to taxation and the economic effects related to it allows the verification of the influence of Equality and Liberty over taxation. From these principles derives the Competitive Neutrality of Constitutional Tax Law, which conforms the use of Extrafiscality instead of antagonizing it, in addition to regulating the act of taxation. Inspired by its European counterpart, the Neutrality that arises from the Brazilian constitutional tax order is more comprehensive precisely because of its connection with equal conditions of competition in the market and with Free Enterprise. This idea of Neutrality, however, should not be confused with the constitutional concept of Free Competition, since the first is an individual freedom, while the second is a collective one.